The battle of Cuito Cuanavale (1987-1988): The war for its memory (Tempo e Argumento, 2021)
In 1987, President’s José Eduardo dos Santos government of Angola was committed to end UNITA and South Africa's operations in Southwest Africa. Assisted by Russian military advisers, FAPLA started a major military offensive and, due to the inexperience of advisers and the rapid reaction by UNITA and supported by SADF, the combined Angolan forces retreated to the small village of Cuito Cuanavale. After days of siege, the Cuban Army intervened in favor of FAPLA, completely reversing the outcome of the battle that decided the future of three countries. In this sense, the present article aims to understand how it ended and how the memory around it became the reason of dispute between the contenders.